Effect of bardoxolone methyl on the lower reproductive tract microbiome in turkey breeder hens - Nabthonglang, Juthamas; Gomez, Andres; Rutschke, Stephanie; Santativongchai, Pitchaya; Kosonsiriluk, Sunantha; Studniski, Marissa; Wileman, Ben; Navanukraw, Chainarong; Boukherroub, Kahina (Frontiers in Physiology, 2025)
IntroductionFertility decline in aging turkey breeder hens is associated with reduced sperm storage in the uterovaginal junction (UVJ), inflammation, oxidative stress, and tissue aging. The mucosal microbiome is an important contributor to subfertility, with shifts in immune function, inflammation, and oxidative stress linked to microbial changes. Bardoxolone methyl, a potent activator of the nuclear erythroid 2-related factor 2 (NRF2) pathway, enhances antioxidant defenses and reduces inflammation. This study investigated if bardoxolone methyl treatment alters the microbial composition and diversity of the UVJ and vagina in turkey hens.MethodsForty turkey hens (59 weeks old) were randomly assigned to a bardoxolone methyl group (n = 20) or a control group (n = 20). Birds received intramuscular tail injections of bardoxolone methyl or vehicle, every other day for two weeks. Swabs from the UVJ and vagina (VAG) were collected for 16S rRNA sequencing. Microbial diversity, differential taxonomic composition, and predicted functional pathways were assessed using QIIME2, PICRUSt2, and R-based statistical packages. Microbiome profiles revealed significant differences between UVJ and VAG communities. ResultsThe VAG showed higher bacterial richness, while both sites were dominated by Firmicutes, Proteobacteria, Thermoproteota, and Actinobacteriota phyla, indicator species analyses identified enrichment of Staphylococcus and Escherichia in UVJ, and Lactobacillaceae in VAG. Bardoxolone methyl did not significantly alter global alpha diversity but selectively modulated unweighted beta diversity and low-abundance taxa, enriching Corynebacterium in UVJ and rare taxa like Armatimonadota and Omnitrophota in the VAG. Functional predictions indicated bardoxolone methyl’s association with enrichment of pathways including energy metabolism, nucleotide biosynthesis, protein quality control, and redox balance, particularly in the UVJ.DiscussionThis study provides the first characterization of the turkey lower reproductive tract microbiome, revealing tissue-specific communities and functional profiles between the UVJ and vagina. Bardoxolone methyl treatment did not alter overall microbial diversity, but selectively enriched low-abundance taxa and metabolic pathways related to energy metabolism, nucleotide biosynthesis, and stress resilience, particularly in the UVJ. These findings indicate that bardoxolone methyl treatment can finetune microbial functional capacity without destabilizing overall community structure. The results also highlight the importance of considering tissue-specific differences and functional potential when investigating reproductive function.